The Euro-bank, its origins, management, and outlook - Davis, Steven I. (New York : Wiley, 1976)
The purpose of this book is to analyse today's generation of Euro-banks from the perspective of management to determine how these banks are dealing with the critical issues they faced in the mid-1970s
"A Halsted Press book."
Includes index.
Bibliography: p. [122]-123.
osc 8/5/18
Loans
Keywords: Banks and banking, International; Euro-dollar market